Technical performance of Plant Clinics as providers of crop protection services: The case of Guilan Province, Iran. (November 2017) - Azimi, Roya; Allahyari, Mohammad S.; Damalas, Christos A.; Kavoosi-Kalashami, Mohammad
Abstract: Plant Clinics offer significant services to small-scale farmers in terms of crop protection advice in many developing countries, but research pertaining to the technical performance of Plant Clinics as providers of crop protection services is limited. The present study evaluated the performance of Plant Clinics in Guilan Province of northern Iran by data envelopment analysis (DEA). Data were collected through a structured questionnaire from paddy farmers and the executives of eighteen Plant Clinics in Guilan Province in northern Iran. Most Plant Clinics (61.1%) covered an area from 400 to 800 ha and most (83.3%) served up to 800 farmers, issuing between 1 and 50 prescriptions annually. The number of staff in the majority of Plant Clinics (55.6%) was between 5 and 10 people. Most Plant Clinics (55.6%) had an annual income between 150 and 250 million Iranian rials (IRR). Among 18 Plant Clinics studied, nine units had efficient performance, whereas the remaining showed inefficient operation. Efficient units tried more to absorb resources, to optimally allocate them, and to provide optimum services. Moreover, efficient units were more oriented towards clients' satisfaction and income promotion, which improved the units' efficiency. Benchmarks were then determined for the inefficient Plant Clinics, so that the managers of those clinics can have insights into the status of those units compared with other Plant Clinics and try to fix their weaknesses and better exploit their strengths. Findings provide a framework for the evaluation of Plant Clinics as providers of crop protection services. Apart from local significance for improving the operation of Plant Clinics in Guilan Province, findings reveal critical points of intervention for improving Plant Clinics performance in other developing countries where these units operate. Highlights: Plant Clinics in Guilan Province were evaluated by data envelopment analysis (DEA). Nine units showed efficient performance, whereas the remaining nine were inefficient. Efficient Plant Clinics tried more to absorb resources and to provide optimum services. Efficient units were more oriented towards clients' satisfaction and income promotion. Findings reveal critical points of intervention for improving Plant Clinics' performance.